A study on translanguaging between Malaysia and China primary schools’ students in ESL writing classroom - Ramakarsinin, Grace Gayathri; Qi, Zhou Xiao; Maniam, Mahendran (International Journal of Asian Social Science, 2024)
This research investigates the efficacy of translanguaging on writing ability and the attitudes of students from Malaysia and China in English lessons. Writing ability, a combination of various skills, is explored through a mixed-method approach with a purposive sampling of 20 students—10 from Malaysia and 10 from China. Interviews were conducted with two teachers and three students from a Malaysian sub-urban school, and a teacher and two students from a primary school in China to gather qualitative data. The study also used a pre-experimental design, employing pre- and post-tests to assess the quantitative aspect. The findings suggest that classroom culture plays a crucial role in fostering positive attitudes toward multilingualism and second language acquisition. Translanguaging allowed students to bridge the gap between their home language (L1) and school language (L2), resulting in improved writing outcomes, particularly for students with low proficiency. It also led to more authentic, well-constructed work. However, some teachers expressed concerns about the influence of translanguaging on students’ writing, particularly the risk of substituting L1 strategies for English ones. Despite these concerns, the research demonstrates that translanguaging can be a valuable tool for enhancing writing ability and building positive attitudes towards language learning.